ANALISIS TERJEMAH AYAT-AYAT ISTIFHÄ€M: Studi Terhadap Al-Qurâ€™an & Terjemahnya Kemenag RI Edisi 2002 - Dakwah Dinuro; Abdul Ghofur Maimoen (AL ITQAN: Jurnal Studi Al-Qur'an, 2019)
Al-Qur`an is a medium of interaction between God and humans by using Arabic. This interaction uses a variety of sentences, including an interrogative sentence. The interrogative sentence does not only function to ask for information but is intended for other purposes according to the context of the narrative. People who do not speak Arabic, how to understand the interactions contained in the Qur'an depends on the translation into their language. This study examines the Indonesian Ministry of Religious Affairâ€™s translation of IstifhÄm verses with a focus on surah al-Baqarahjuz 1. The method used in this study is descriptive-analysis method witha translation theory for IstifhÄm verses or introgative sentences. This method is used to determine the consistency of the translation and the value represented in the translation. This study concludes that the translation is consistent in selecting equivalent words. Meanwhile, inconsistencies occur in the translation of the question word hamzah by thereason of Â more appropriate considered diction for the translation. Sometimes hamzah is translated using the question word "apakah (whether)", the particle "kah", "mengapa (why)", and "tidak (not)". In general, the 11 verses, the object of the author's study, are translated into the form of interrogative sentences. Keywords: IstifhÄm, translation, Al-Qur`an, tafsir